Effect of Foliar Spray Application of Zinc Oxide Nanoparticles on Quantitative, Nutritional, and Physiological Parameters of Foxtail Millet (Setaria italica L.) under Field Conditions - Kolenčík, Marek; Ernst, Dávid; Komár, Matej; Urík, Martin; Šebesta, Martin; Dobročka, Edmud; Černý, Ivan; Illa, Ramakanth; Kanike, Raghavendra; Qian, Yu; Feng, Huan; Orlová, Denisa; et al. (Nanomaterials (Basel, Switzerland), 2019)
It has been shown that the foliar application of inorganic nano-materials on cereal plants during their growth cycle enhances the rate of plant productivity by providing a micro-nutrient source. We therefore studied the effects of foliarly applied ZnO nanoparticles (ZnO NPs) on Setaria italica L. foxtail millet's quantitative, nutritional, and physiological parameters. Scanning electron microscopy showed that the ZnO NPs have an average particle size under 20 nm and dominant spherically shaped morphology. Energy dispersive X-ray spectrometry then confirmed ZnO NP homogeneity, and X-ray diffraction verified their high crystalline and wurtzite-structure symmetry. Although plant height, thousand grain weight, and grain yield quantitative parameters did not differ statistically between ZnO NP-treated and untreated plants, the ZnO NP-treated plant grains had significantly higher oil and total nitrogen contents and significantly lower crop water stress index (CWSI). This highlights that the slow-releasing nano-fertilizer improves plant physiological properties and various grain nutritional parameters, and its application is therefore especially beneficial for progressive nanomaterial-based industries.
Keywords: zinc-oxide nanoparticles; foliar application; quantitative, nutritional, and physiological parameters; nano-fertilizers; foxtail millet